Ethnobotanical Documentation Of Wild Edible Fruits Used By Muthuvan Tribes Of Idukki, Kerala- India - T.P AJESH; S.A ABDULLA NASEEF; R. KUMUTHAKALAVALLI (International Journal of Pharma and Bio Sciences, 2012)
Throughout history, wild edible plants have sustained human populations in each of the inhabited continents. Human consumption of wild plants has been documented from antiquity into the common Era. Dietary use of wild fruits, nuts, seeds, and leaves appear in numerous historical records. Today, most human plant foods are based on a rather limited number of crops. However, it is clear that in many parts of the world, the use of wild plants is not negligible. In India, the indigenous fruits collected from the wild play a significant role in the food and nutrient security of rural poor and tribals. Some wild fruits have been identified to have better nutritional value than cultivated fruits. The present communication deals with the ethnobotanical exploration, identification, concerns and future potentialities of the wild edible fruits consumed by the Muthuvan tribes inhabiting the hilly areas of Idukki district of Kerala. Thirty eight species of wild edible fruits belonging to 25 genera and 17 families used by Muthuvans were recorded. Due to the climate change, the level of poverty, and environmental degradation, there is a high risk of biodiversity loss at a large scale. Under such circumstances, the knowledge and uses of nutritious, climatically adapted wild edible fruits will be irreversibly lost. Hence, research attention is needed to increase awareness on the use and management of wild edible fruits for their conservation.